Geophysical siting of boreholes in crystalline basement areas of Africa (1992)
This paper assesses the effectiveness of surface geophysical methods namely electrical resistivity, electromagnetic, seismic refraction, magnetic, gravity and induced polarization for groundwater exploration in crystalline basement complex areas. Most of these geophysical techniques can provide quantitative information on the characteristics of the weathered zone which relate to the occurrence of an economic aquifer. The critical factors in the choice of a particular method include the local geological setting, the initial and maintenance costs of the equipment, the speed of surveying, the manpower required as field crew, the degree of sophistication entailed in data processing to enable a geologically meaningful interpretation, and anomaly resolution. The particular advantages and limitations of each technique are highlighted. Several case histories from Nigeria and the rest of Africa indicate that electrical resistivity (both vertical sounding and horizontal profiling) is the most widely used, followed by electromagnetic traversing. These are often employed in combination to improve upon the percentage of successful boreholes. Due to the high cost of equipment, large scale of the field operations and difficulties in data interpretation, seismic refraction is not widely adopted in commercial- type surveys. Similarly, magnetic, gravity and induced polarization are used only sparingly